Acoustic determination of thermophysical properties and critical parameters for the mixture (51 wt% R143a+ 49 wt% R125) and critical line of x CO2+(1− x)(51 wt% R143a+ 49 wt% R125) - Esperança, José M. S. S. (2021)
The thermophysical properties and critical parameters for the alternative refrigerant (51 wt % of 1,1,1-trifluoroethane (R143a) + 49 wt % of pentafluoroethane (R125))svery close to the composition of R507 (50 wt % of each mixture component)swere investigated using two different acoustic techniques. The critical behavior of the system xCO2 + (1 - x)(51 wt % R143a + 49 wt % R125) was also investigated. Experimental data of speed of sound in liquid (51 wt % R143a + 49 wt % R125) from T ) (253 to 338) K and pressures up to 65 MPa were measured using a pulse-echo method. Derived thermodynamic properties were calculated, combining our experimental data with density and isobaric heat capacity values published by other authors. Measurements of the critical temperature Tc and pressure pc on (51 wt % R143a + 49 wt % R125) and mixtures of xCO2 + (1 - x)(51 wt % R143a + 49 wt % R125) were performed using another simple ultrasonic time-delay technique. The binary critical line was determined over the whole composition range showing that this system deviates only slightly from ideality since the critical line is a continuous line. The Peng-Robinson equation of state with conventional mixing and combining parameters was used to correlate the binary experimental data.